Social security tax and endogenous technical change in an economy with an aging population - Codrina Rada (The University of Utah, Department of Economics, 2011)
This paper presents a classical model of economic growth which incorporates class conflict and induced technological change to show how demographic changes can affect future income distribution and production relations in industrialized countries. Specifically, I use an extended real wage Phillips curve to account for the effects of a social security tax on income distribution and therefore on capital accumulation and employment. In this framework output growth is determined from the supply side by available savings. Analytical and simulation results indicate that the sustainability of an economy with fast population aging over transient paths hinges upon improvements in labor productivity, hence, the specific mechanism of technical progress in place.
Keywords: E62; E24; O30; 330; Population aging; Social security tax; Endogenous technical change